Higher prevalence of irritable bowel syndrome and greater gastrointestinal symptoms in obsessive-compulsive disorder. (November 2019) - Turna, Jasmine; Grosman Kaplan, Keren; Patterson, Beth; Bercik, Premysl; Anglin, Rebecca; Soreni, Noam; Van Ameringen, Michael
Abstract: Background: Anxiety and mood symptoms often co-occur with gastrointestinal problems, such as irritable bowel syndrome (IBS). The extent to which these relate to Obsessive-Compulsive Disorder (OCD) is unclear, despite anxiety being a prominent symptom of this disorder. The purpose of this analysis was to examine gastrointestinal symptoms in unmedicated, non-depressed adult OCD patients compared to age- and sex-matched community controls. Methods: Twenty-one OCD patients and 22 controls were recruited from the community (Hamilton, ON, Canada) and enrolled in this cross-sectional study. In addition to a standardized psychiatric assessment, participants completed clinician- and self-rated psychiatric and gastrointestinal symptom severity measures. Presence of IBS was assessed using Rome III criteria. Results: Gastrointestinal symptom severity (GSRS total; OCD = 8.67 ± 6.72 vs. controls = 2.32 ± 2.12) and prevalence of IBS (OCD = 47.6%; Controls = 4.5%) was higher in OCD patients than in controls. A comparison of OCD patients based on IBS status revealed greater depressive symptom severity (total MADRS: 12.60 ± 1.89 vs 6.91 ± 2.77), p < 0.001) among those with IBS. Conclusions: High prevalence and severity of gastrointestinal symptoms may be an important clinical consideration when treating OCD patients. More specifically, assessment of IBS and gastrointestinal symptoms may be useful when considering pharmacotherapeutic treatments options for patients. Given the high comorbidity noted with IBS, a disorder of the "gut-brain axis", results may suggest a shared pathophysiological mechanism between psychiatric and gastrointestinal disorders which should be explored in future research.